PRE-SERVICE ENGLISH TEACHERS’ ATTITUDE TOWARDS STUDENTS’ WILLINGNESS TO COMMUNICATE - Amalia, Suci Nugrah; Asib, Abdul; Marmanto, Sri (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
The present instrumental case study focused on probing into pre-service English teachers’ attitude towards students’ willingness to communicate (WTC). 10 pre-service English teachers were purposively chosen regarding their familiarity and comprehension with the study issue. The data were solicited from interview and questionnaire. Their attitude was manifested in their positive evaluative judgments towards the hypothesized model of WTC whereby those judgments also represented three domains of attitude subsuming affective, cognitive, and behavioral domain. The results indicated that in spite of some situational restrictions, all of the participants had a positive attitude towards students’ WTC which guides them to carry out communicative learning activities in the classroom. Further studies are highly recommended to more deeply deal with the realm of WTC implementation in Indonesian contexts. Such studies can be meaningful references for Indonesian English teachers to encourage students to have a high WTC.